2020
DOI: 10.1186/s41747-019-0129-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided interventions with augmented reality in situ visualisation: a proof-of-mechanism phantom study

Abstract: Background Ultrasound (US) images are currently displayed on monitors, and their understanding needs good orientation skills. Direct overlay of US images onto the according anatomy is possible with augmented reality (AR) technologies. Our purpose was to explore the performance of US-guided needle placement with and without AR in situ US viewing. Methods Three untrained operators and two experienced radiologists performed 200 US-guided punctures: 100 with and 100 without AR in situ US. The punctures were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 22 publications
0
28
1
Order By: Relevance
“…29 Another study by Amacker et al used the HoloLens for ultrasound-guided needle placement on the leg and vessel phantoms. 30 These preliminary studies demonstrated the potential use of improving the operator's spatial orientation. Similar studies have shown the usage of the HoloLens in lumbar facet joint injections, 31 CT-guided lesion targeting, 32 and radiofrequency ablations for liver tumours.…”
Section: Introductionmentioning
confidence: 94%
“…29 Another study by Amacker et al used the HoloLens for ultrasound-guided needle placement on the leg and vessel phantoms. 30 These preliminary studies demonstrated the potential use of improving the operator's spatial orientation. Similar studies have shown the usage of the HoloLens in lumbar facet joint injections, 31 CT-guided lesion targeting, 32 and radiofrequency ablations for liver tumours.…”
Section: Introductionmentioning
confidence: 94%
“…93 Artificial intelligence algorithms promise automated needle tracking and dynamic updating of image plane adjustments for constant visualization of the needle profile in the image plane. Holographic lenses and three-dimensional holograms, 94 as well as virtual and augmented reality, 95,96 may improve target visualization and appreciation of regional anatomy, targeting, training, and operator confidence. 97,98…”
Section: Future Directionsmentioning
confidence: 99%
“…Overcoming such issues entails using AR HMDs to simplify the learning and performing of ultrasound-guided interventions [19][20][21][22]. Head-mounted displays (VST in [19][20][21] and OST in [22]) are used to visualize data from a 2D ultrasound probe.…”
mentioning
confidence: 99%
“…Overcoming such issues entails using AR HMDs to simplify the learning and performing of ultrasound-guided interventions [19][20][21][22]. Head-mounted displays (VST in [19][20][21] and OST in [22]) are used to visualize data from a 2D ultrasound probe. The ultrasound image is directly superimposed on the patient's anatomy in a 1:1 ratio so that the hand-eye coordination process is simplified as "the operator can directly aim the tip of the needle into the ultrasound image" [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation